A review of implicit and explicit substance self-concept as a predictor of alcohol and tobacco use and misuse. (4th May 2017) - Lindgren, Kristen P.; Neighbors, Clayton; Gasser, Melissa L.; Ramirez, Jason J.; Cvencek, Dario
ABSTRACT: Background : This paper provides an overview of the self-concept as it relates to substance use. Self-concept has a long history in psychological theory and research; however, substance self-concept (e.g., viewing one's self as a drinker or smoker) is an understudied area of research with the potential to expand existing conceptualizations of substance use, addiction, and prevention and treatment efforts, and should receive greater research attention. Objectives : First, we review and provide a theoretical framework of substance self-concept that draws from dual process models and distinguishes between implicit and explicit self-concept. Next, we summarize key findings related to substance use in the extant literature, focusing on alcohol and tobacco (smoking). Results : Across both substances, there is converging evidence that substance self-concept is associated with substance use outcomes, including quantity and frequency of use and problems associated with use, and that change in substance self-concept is associated with recovery from substance misuse. Recommendations for the substance self-concept research agenda include routine assessment of substance self-concept, expanded use of implicit measures, investigation of moderators of substance self-concept, and targeting substance self-concept directly in prevention and intervention efforts. Conclusion : Ultimately, we suggest that substance self-concept is a promising, but understudied, construct. Greater research attention to substance self-concept could clarify its potential as an important risk factor for hazardous use and addiction as well as its utility as a prevention and treatment target.